2013
DOI: 10.1007/s00221-012-3388-x
|View full text |Cite|
|
Sign up to set email alerts
|

Dependency of human neck reflex responses on the bandwidth of pseudorandom anterior-posterior torso perturbations

Abstract: The vestibulocollic (VCR) and cervicocollic (CCR) reflexes are essential to stabilize the head-neck system and to deal with unexpected disturbances. This study investigates how neck reflexes contribute to stabilization and modulate with perturbation properties. We hypothesized that VCR and CCR modulate with the bandwidth of the perturbation and that this modulation is maintained across amplitudes and influenced by the eyes being open or closed. Seated subjects were perturbed in an anterior-posterior direction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 51 publications
8
39
1
Order By: Relevance
“…gain > 1, left axis, Figure 3) and studies agree on interpretations of this as an effect of mechanical resonance (Forbes et al, 2013;Goldberg and Peterson, 1986;Peng et al, 1996), meaning that the oscillatory response of a system is larger than the imposed perturbation. The Eigen-frequency of a system determines the threshold for mechanical resonance and depends on the systems mass and viscoelastic properties.…”
Section: Responses Above 2hzsupporting
confidence: 62%
“…gain > 1, left axis, Figure 3) and studies agree on interpretations of this as an effect of mechanical resonance (Forbes et al, 2013;Goldberg and Peterson, 1986;Peng et al, 1996), meaning that the oscillatory response of a system is larger than the imposed perturbation. The Eigen-frequency of a system determines the threshold for mechanical resonance and depends on the systems mass and viscoelastic properties.…”
Section: Responses Above 2hzsupporting
confidence: 62%
“…The experimental protocol and data analysis were similar to a previous study where healthy volunteers showed a profound modulation of stabilization strategies with perturbation bandwidth (Forbes et al,2013). In short, subjects were restrained by a four-point harness to a rigid chair with a 10° inclined backrest mounted on a motion platform and exposed to…”
Section: Methodsmentioning
confidence: 99%
“…1 (Forbes et al,2013;Kearney et al,1997;Mirbagheri et al,2000;Schouten et al,2008), likely to prevent oscillatory behaviour as a result of the time delay within afferent feedback loops. Subsequently, in this study we adopted the lowest bandwidth (0.2-1.2) and highest bandwidth (0.2-8 Hz) perturbations from Forbes et al (2013) with minor modifications described below. Exposing both patients and controls to these two perturbations while performing head-neck stabilization tasks allowed us to examine our hypothesis of impaired afferent feedback modulation in patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations